Kualitas Pelayanan dalam Mendukung Kinerja Gabungan Kelompok Tani di Kabupaten Merauke - David Laiyan; Elisabet Permaisela Suhardi; Paul Adryani Moento (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
Public service is a concrete action taken by a group of rang to create a good workflow that demands professionalism and empathy to create a predetermined goal. This research was conducted in the village of Prudence. The purpose of this study is to review and know the quality of service in supporting the performance of Gapoktan Lumbung Sehati sloping land district merauke regency. The research method used in this study is qualitative, which is to gain an understanding of an event on the ground about human actions under certain conditions translated according to the researcher's thinking. This type of research is qualitative descriptive. Then the data collection technique is done by conducting obesitrvasi to the first research place, then conducting interviews with several informants and documentation of the results of the study. The results showed that the quality of service, namely the actions of gapoktan managers, was good. The leader of the peasant group provides information when there are things that are considered important to create a conducive peasant group atmosphere. Then, a combination of farming groups is always listening to complaints and providing solutions or taking action to answer the complaints. And from the aspect of responsibility gapoktan has carried out obligations in fulfilling the duty of service to the members even though it is not yet maximal.